Sobre a semântica do verbo ’ficar’ em construções progressivas com adjetivos e particípios - Rebouças, Rute (Revista da Associação Portuguesa de Linguística, 2021)
The Portuguese language, unlike many other languages, has the verb ficar, which is often used in resultative constructions and is characterized by having a multifunctionality: staying in a certain place, presenting the result of a change or an aspectual operation (ficar a + infinitive). In this way, this work aims to study the behavior of the verb ficar, as an indicator of change, in progressive constructions with adjectives and participles, to characterize not only the verb ficar and the progressive constructions, but also the adjectives and participles that occur in them. To this end, we selected examples of two distinct corpora built with adjectives and participles, whose tense of “estar a” would be in one of following: Presente, Pretérito Perfeito and Imperfeito (Simples do Indicativo). So, the observation of the selected tenses that occurred in these constructions, the type of adjective and its possible graduation, as well as some participles and their proximity to the typical characteristics of the adjectives, were considered as essential aspects for the development of this study. In this work, it was possible to conclude that the presence of the verb ficar in progressive constructions seems to demonstrate the loss of the characteristic completeness and resultative meaning of this verb, presenting the progressive a progression which seems to prevail. Besides, it was also possible to conclude that ficar in these constructions, selects mainly adjectives and that the selected tense is mostly Presente do Indicativo